ANALYSIS OF SOCIAL INFLUENCE, FINANCIAL LITERACY, AND SAVING BEHAVIOUR ON STUDENTS IN BANDUNG CITY USING SELF-CONTROL AS A MODERATION VARIABLE - Dwi Lestari Ayuningsih; Andrieta Shintia Dewi (SEAN Institute, 2023)
Financial literacy is essential for effectively managing and making financial decisions. Indonesia has a poor degree of financial literacy, which leads to excessive consumption. Supported by Consumer Survey conducted by Bank Indonesia show the level of saving behaviour in society is still low. Students as an element tend not to have good financial management skills and become consumptive. This study aims to analyze the influence of social influence, financial literacy, saving behaviour, and self-control as moderating variable on students in Bandung City. In research, quantitative methods are used. The data were collected from 400 Bandung students aged 18 to 25 and analyzed using Partial Least Squares (PLS) Structural Equation Modeling (SEM). This study found that social influence had significant effect on financial literacy, financial literacy influences saving behaviour, financial literacy mediates the relationship between social influence and saving behaviour, and self-control moderates the relationship between financial literacy and saving behaviour.